Shaping the future of nanotechnology: a perspective on education, dissemination and ethics - Díaz-Marcos, Jordi; Mendoza Gonzálvez, Joan (Frontiers in Nanotechnology, 2025)
Considering the potential economic, technological, and scientific impacts, Nanosciences and Nanotechnologies (N&N) have sparked interest across numerous sectors of society. The anticipated benefits in areas such as manufacturing, water and environmental pollutant purification, improvements in energy production, storage and distribution systems, and enhancements in food and health systems, among others, suggest that the development and exploitation of new nanomaterials, nanotools, and nanodevices could have an impact of billions of euros in the next decade. Concurrently, an increasing number of companies worldwide are implementing research and development (R&D) programs in N&N. It is expected that, in the next decade, governments and corporations combined will spend more than 10,000 million euros on N&N R&D. This implies that for a modern society to access these benefits and contribute to this scientific and technological revolution, it is necessary to have programs that support the training of high-level professionals in N&N. These professionals need to be equipped to successfully meet the needs arising from market and societal challenges and opportunities; designing, producing, or developing products that innovatively contain and exploit nanomaterials and devices derived from N&N, ensuring these products are appropriately integrated into everyday life. It is estimated that more than 1,000,000 professionals in the field will be required worldwide. Therefore, in the last two decades, educational institutions around the world, particularly in the European region, have explored various strategies to incorporate N&N related topics into the educational curriculum, from generating terminal areas in traditional science and engineering programs to creating new academic programs (at undergraduate and postgraduate levels) that allow them to contribute to the training of competitive human resources in N&N. Disseminating and educating about nanoscience and nanotechnology (N&N) presents significant challenges. The subject is inherently complex and characterized by dense terminology. Additionally, the nanoscale dimension introduces unique dissemination difficulties. For instance, materials at this scale are only observable with highly sophisticated instruments, necessitating that audiences comprehend concepts of objects they cannot directly see. Nevertheless, the widespread presence of nanoscale products offers compelling examples that can facilitate the dissemination of nanotechnologies. The highly anticipated nanotechnological revolution of the 21st century raises numerous questions that delve into the essence of both the nanotechnological phenomenon and the human condition. What truly distinguishes nanotechnology, and what challenges does this innovation pose for humanity? Unlike previous technologies, discussions about new technologies now commence at their inception, enabling proactive measures. It is crucial to strike a balance, avoiding both excessive optimism and dire pessimism. Nanotechnology initiatives, regarded as highly significant social activities in today’s world, necessitate careful consideration. This perspective urges us to adopt appropriate ethical frameworks to effectively address the challenges posed by nanotechnologies. In this article, we provide an overview of the dissemination and scientific communication of nanotechnologies. We analyze the available tools and highlight the current state of nanodissemination through a comprehensive review of mature and successful dissemination initiatives in nanosciences and nanotechnologies. Additionally, we include an ethical reflection on how to approach the advancement of nanoscience and nanotechnology. Furthermore, based on the conclusions of this work, we offer recommendations and best practices for dissemination, education, and fostering an appropriate ethical perspective on the present and future of nanosciences and nanotechnologies.